Democracy in the Inter-American System: A Look into the Inter-American Democratic Charter Sixteen Years after its Adoption - Negro Alvarado, Dante Mauricio (2018)
The purpose of this paper is to analyze the application of some articles of the Inter-American Democratic Charter, especially those contained in Chapter IV of that instrument entitled “Strengthening and preserving democratic institutions.” Although the Charter is not the only document that aims to promote and defend representative democracy within the framework of the OAS, it is perhaps the most important one and, at least, the one that has been applied extensively in the region in the last sixteen years. We will mainly address the various situations that must be configured for the application of the Charter and the competencies of the various actors and organs of the Organization in relation to it, all of them within the scope of that chapter IV.